Dysarthria following Stroke - Spencer, Kristie A.; Brown, Katherine A. (Seminars in Speech and Language, 2018)
Dysarthria is a common consequence of stroke and can have a detrimental influence on communication and quality of life. Speech-language pathologists (SLPs) play an important role in the evaluation and rehabilitation of stroke survivors who present with dysarthria. An understanding of the physiologic reason behind the altered speech characteristics, such as weakness or incoordination, can facilitate differential diagnosis, guide evaluation strategies, and influence treatment approaches. An initial comprehensive speech evaluation is comprised of examination of the speech mechanism, screening of speech subsystems, perceptual assessment, and intelligibility measurement. Management strategies focus on optimizing communication through compensatory strategies as well as providing physiologic support. The SLP is also responsible for educating family and staff regarding strategies that can facilitate communication.
Keywords: Dysarthria; stroke; evaluation; management; treatment